PENERAPAN METODE FULL COSTING PADA SISTEM INFORMASI HARGA POKOK PRODUKSI PADA DAHAN KONVEKSI - Bryan Samuel Bangonan; Afifah; Husni Angriani (STMIK KHARISMA Makassar, 2019)
Base cost of production is very important on counting profit and loss of the company. If the company is not thorough or incorrect in counting the cost of production, it can lead to error in determining the profit and loss that the company obtained. It is very important to correctly determine the base cost of production. The tight competition in the market forces one company to compete with another in producing product or service, which leads to the importance of obtaining information regarding the cost and the base cost of production to help make the right decision. This research is intended to provide a computerized system that can help Dahan Konveksi in determining the base cost of production to decide on the cost of goods sold using the Full Costing method. Based on the production cost on December, it was determined that the base cost of production will be Rp 59.435. From that result, it was decided that the target selling price will be Rp 95.096. Using the Full Costing method, where fixed cost and variable cost are excluded, selling price per sheet is obtained. It can also be a basic cost in determining the selling price target.